Thursday

November 27, 2014

November 27, 2014

Posted by **Laura** on Wednesday, November 14, 2012 at 10:15pm.

- Math -
**Reiny**, Wednesday, November 14, 2012 at 10:45pmlet y = (x+2)/(x-1)

first step in finding the inverse is to interchange the x and y variables, so

inverse is

x = (y+2)/(y-1)

now solve this for y

xy-x = y+2

xy - y = 2+x

y(x-1) = 2+x**y = (x+2)/(x-1)**

test with some x and y

in original , let x = 2

then y = 4/1 = 4

in new equation , let x = 4, should get y = 2

y = (4+2)/(4-1) = 6/3 = 2

yeah!!!!

**Answer this Question**

**Related Questions**

Math - Determine whether each equation is true for all x for which both sides of...

algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

math - Determine the inverse of f(x)=(x^3)-2 Is the inverse the switch of ...

Pre-Calc - Does y=1/x have an inverse? It is a one-to-one function, so it should...

Inverse of log function - Find the inverse of f(x) = log(2+x) - 4 the base is "a...

Algebra II (Matrices) - My book doesn't solve it like a linear equation, they ...

inverse equation - How is any equation of the form y= -x + b its own inverse?

Algebra - what is the inverse of the linear parent function? How would you graph...

math help1 - Okay I am a little bit confused about one math question can you ...

math - The cost of producing q articles is given by the function C=f(q)=100+2q...